Critical spatial requirement within the origin of simian virus 40 DNA replication. - Cohen, G L (1984)
We inserted a single base pair into the center of a 27-base-pair palindrome within the replication origin of simian virus 40. The mutation did not directly alter the symmetry of the palindrome or the protein-binding sequences within the palindrome. DNA binding studies showed that subunits of the simian virus 40 A protein (T antigen) bound to each of the four recognition pentanucleotides in the origin palindrome but did so with reduced affinity in comparison with wild-type origins. The mutant origin cloned in a plasmid DNA failed to replicate in COS cells. Thus, precise spatial interactions among subunits of A protein are necessary for stable origin binding and are crucial for subsequent steps in the initiation of DNA replication. Furthermore, any possible functional interactions of the simian virus 40 A protein with cellular DNA would require a great fidelity of protein binding arrangements to initiate cellular DNA replication.